Effect of temperature on bio-oil characteristics in pyrolysis of Sunan candlenut olicake - Rajendra, I Made (International Journal of Engineering and Emerging Technology, 2022)
This study aims to determine the effect of temperature on the characteristics of bio-oil on the pyrolysis of Sunan candlenut oilcake (SCO). SCO is the waste that arises from the compression of the Sunan candlenut seeds in the biodiesel production process, which can be converted into bio-oil as a raw material for bio-fuel. Furthermore, to obtain bio-oil, SCO was pyrolyzed in a fixed bed reactor and the temperature varied at 250,350, 450, 550, and 650 o C to find the best conditions. The bio-oil was tested for the properties of the hydrocarbon compounds contained using gas chromatography-mass spectrometry (GC-MS) and then compared. The results show that the percentage of hydrocarbons increases with increasing temperature. The bio-oil from the pyrolysis of SCO contains more than 70% hydrocarbon compounds at temperatures above 450 o C. Aromatic hydrocarbon increases with increasing temperature and are stable from 550 o C. Based on the results, it can be stated that the pyrolysis of SCO with the aim of obtaining bio-oil with optimum hydrocarbons content can be carried out at temperature intervals of 450 to 550 o C.